Contemporary distribution of benthic foraminiferal assemblages in coastal wetlands of south-eastern Australia. (30th October 2020) - Lal, Kirti K.; Bonetti, Carla; Woodroffe, Colin D.; Rogers, Kerrylee
Abstract: Benthic foraminifera identified from the upper intertidal zone of coastal mangrove and saltmarsh wetlands of south-eastern Australia exhibit spatial zonation that varies with elevation and corresponds to position in the tidal frame. This study describes relationships between benthic foraminiferal assemblages and environmental variables, such as wetland elevation, pore-water salinity, substrate organic matter content and sediment grainsize. Agglutinated taxa dominated higher in the tidal frame, whereas calcareous taxa increased in both relative abundance and diversity lower in the tidal frame. Species composition varied within and between study sites, reflecting local differences in other environmental variables. Three major spatial clusters were identified in the upper intertidal zone from a dataset consisting of 111 contemporary samples: a high-to mid-elevation assemblage consisting of differing abundances of Entzia macrescens and Trochammina inflata ; a mid-elevation assemblage comprised of Arenoparrella mexicana in association with Trochammina inflata and Quinqueloculina seminula ; and mid-to low-elevation assemblage characterised by Cribroelphidium excavatum, Quinqueloculina seminula, Ammobaculites spp. and Miliammina fusca. Multivariate analysis correlated foraminiferal assemblages with environmental variables showing that foraminiferal distribution in the region is constrained primarily by wetland elevation, but also by pore-water salinity. Foraminiferal assemblages derived from cluster analysis correlated with vegetation zones, implying that both foraminifera and vegetation are influenced by elevation and salinity. This paper seeks to demonstrate that the consistency in spatial zonation of assemblages provides greater confidence that contemporary distribution of foraminiferal assemblages can assist with the interpretation of past depositional conditions and palaeo-environmental reconstructions, providing insights into the evolution of coastal wetlands of south-eastern Australia over the Holocene. Highlights: Foraminifera exhibited vertical zonation corresponding to position in the tidal frame Environmental variables has a significant influence on species composition Foraminiferal assemblages correlate with upper intertidal vegetation zones Contemporary foraminiferal assemblages can be used to reconstruct past environments